The Role of Innate versus Adaptive Immune Responses in a Mouse Model of O'Nyong-Nyong Virus Infection - Seymour, Robert L. (The American Society of Tropical Medicine and Hygiene, 2013)
O'nyong-nyong virus (ONNV), an alphavirus closely related to chikungunya virus (CHIKV), has caused three major epidemics in Africa since 1959. Both ONNV and CHIKV produce similar syndromes with fever, rash, and debilitating arthralgia. To determine the roles of the innate and adaptive immune responses, we infected different knockout mice with two strains of ONNV (SG650 and MP30). Wild-type, RAG1 KO, and IFNγR KO mice showed no signs of illness or viremia. The STAT1 KO and A129 mice exhibited 50–55% mortality when infected with SG650. Strain SG650 was more virulent in the STAT1 KO and A129 than MP30. Deficiency in interferon α/β signaling (A129 and STAT1 KO) leaves mice susceptible to lethal disease; whereas a deficiency of interferon γ signaling alone had no effect on survival. Our findings highlight the importance of type I interferon in protection against ONNV infection, whereas the adaptive immune system is relatively unimportant in the acute infection.